External Sustainability : A Stock Equilibrium Perspective - Loayza, Norman, 1964- 1964- (The World Bank, 2000)
The 1994 crisis in Mexico, developments in East Asia, and persistent turmoil in world financial markets have dramatized the role of external imbalances in macroeconomic crises. Some believe that the current account should be kept from rising beyond a sustainable level, some that a current account surplus is the only solid external position. Can those rules of thumb be justified analytically? - Calderón, Loayza, and Servén consider external sustainability from the perspective of equilibrium in net foreign asset positions. Under their approach, an external situation is sustainable if it is consistent with international and domestic investors' achieving their desired portfolio allocation across countries. They develop a reduced-form model of net foreign asset positions whose long-run equilibrium condition expresses the ratio of net foreign assets to the total wealth of domestic residents as a negative function of investment returns in the country relative to the rest of the world, a positive function of investment risk, and an inverse function of the ratio of foreign-owned to domestically owned wealth. To estimate this equilibrium condition, the authors use a newly constructed data set of foreign asset and liability stocks for a large group of industrial and developing countries, from the 1960s to the present. They also develop summary measures of country returns and risks. Their econometric methodology is an application of the Pooled Mean Group estimator recently developed by Pesaran, Shin, and Smith (1999), which allows for unrestricted cross-country heterogeneity in short-term dynamics while imposing a common long-run specification. The estimation results lend considerable support to the model, especially when applied to countries with low capital controls or high or upper-middle income. The results for countries with high capital controls and, especially, lowe...